Exercise protocols for improving functional outcomes in hip fractures - Aborukbah, Abdullah F.; Alfaleh, Taif A.; Alenazi, Haya M.; Alsulami, Asrar K.; Alshahrani, Abdullah A.; Aloraifi, Mohammad A.; Alanazi, Khaled M. (International Journal Of Community Medicine And Public Health, 2024)
Hip fractures, particularly among the elderly, are a growing public health concern due to their association with significant morbidity, mortality, and long-term disability. Effective rehabilitation is essential for restoring mobility, independence, and quality of life in affected individuals. Exercise-based interventions, focusing on early mobilization, strength training, and balance exercises, have been shown to significantly improve functional outcomes in patients recovering from hip fractures. Early mobilization, initiated within 24 to 48 hours post-surgery, reduces the risk of complications associated with immobility, such as muscle atrophy and deep vein thrombosis. Encouraging weight-bearing activities early in the recovery process accelerates the restoration of mobility and functional independence. Strengthening exercises, particularly those targeting the lower extremities, play a crucial role in rebuilding muscle mass and enhancing stability, which is critical for preventing recurrent falls. Balance exercises complement strengthening efforts by improving postural control and reducing the fear of falling, which is common in elderly patients. Long-term adherence to these exercise protocols is vital for sustaining functional improvements and preventing further decline. The long-term outcomes of these interventions extend beyond physical benefits, contributing to improved psychological well-being by promoting confidence and reducing anxiety associated with functional limitations. Tailoring rehabilitation programs to individual needs, ensuring sustained participation, and addressing barriers to adherence, such as lack of access to resources, are crucial for maximizing recovery. These evidence-based strategies offer a comprehensive approach to improving recovery and reducing the long-term burden of hip fractures on individuals and healthcare systems. The integration of structured, progressive exercise regimens, supported by multidisciplinary teams, is key to optimizing both short- and long-term functional outcomes following hip fractures.